2017
DOI: 10.1074/jbc.m117.798827
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylation of Src kinase mediates Src-induced and high-fat diet–accelerated prostate tumor progression in mice

Abstract: Exogenous fatty acids provide substrates for energy production and biogenesis of the cytoplasmic membrane, but they also enhance cellular signaling during cancer cell proliferation. However, it remains controversial whether dietary fatty acids are correlated with tumor progression. In this study, we demonstrate that increased Src kinase activity is associated with high-fat diet-accelerated progression of prostate tumors and that Src kinases mediate this pathological process. Moreover, in the prostate regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 38 publications
1
50
0
Order By: Relevance
“…The collected samples and standards were subjected to liquid chromatography‐mass spectrometry/mass spectrometry (LC‐MS/MS) analysis using an high‐performance liquid chromatography (HPLC) system (with 1100 binary pump) (Agilent, Santa Clara, CA) coupled with a Waters Micromass Quattro Micro triple Quadrupole Mass Spectrometer (Waters, Milford, MA). The details of the simultaneous detection of acyl‐CoAs and internal standard were described in previous publications …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected samples and standards were subjected to liquid chromatography‐mass spectrometry/mass spectrometry (LC‐MS/MS) analysis using an high‐performance liquid chromatography (HPLC) system (with 1100 binary pump) (Agilent, Santa Clara, CA) coupled with a Waters Micromass Quattro Micro triple Quadrupole Mass Spectrometer (Waters, Milford, MA). The details of the simultaneous detection of acyl‐CoAs and internal standard were described in previous publications …”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that a HFD accelerates Src‐mediated tumorigenesis. Particularly, dietary MA significantly increases the biosynthesis of myristoyl‐CoA, expression levels of myristoylated Src, and enhances its kinase activity . PA is a major saturated FA component in a Western diet .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, B13 might target tumor progression in which myristoylation is essential for the "addicted" oncogenic protein in the tumors (48). While cancer cells such as SNU16, KATO III, and MDA-MS-134-VI possess aberrant expression of FGFR1/2, other cancer cells such as PC-3 are dependent on Src kinase activity (26). B13 might serve as an agent for targeting tumor progression driven by the oncogenic pathways in which a myristoylated protein is essential to mediate the oncogenic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates underwent a Click reaction in which the azide functional group on myristoylated proteins was coupled to an alkyne tagged with biotin, allowing detection with streptavidin (Fig. 3C, lane 2 vs. lane 1) (26). Myristoylation is essential for the localization of FRS2α.…”
Section: A Myristoyl-coa Analog B13 Suppresses the Myristoylation Omentioning
confidence: 99%
“…Src is a myristoylated protein and can be found both within and outside of lipid rafts, as well as within endosomes, before translocating to the plasma membrane (Seong et al, 2009). Src can be activated by exogenous saturated fatty acids, such as palmitate and myristic acid, or the overexpression of cluster of differentiation 36 (CD36, also named fatty acid translocase), which is known to facilitate long-chain fatty acid uptake through the myristoylation of Src, leading to activation of its downstream signalling, such as JNK signalling (Holzer et al, 2011;Huang et al, 2017;Kim et al, 2017Kim et al, , 2019Park et al, 2016). Nonetheless, given the increased fatty acid oxidation observed in mice with knockout of Fyn, another Src kinase family member (Bastie et al, 2007), Src activation by ILTV infection may limit viral intercellular spread by balancing host fatty acid metabolism, which can be negated by Src inhibition, resulting in accelerated viral spread and an exacerbated CPE of infection as observed in our model.…”
Section: Discussionmentioning
confidence: 99%